3D MODELING OF THE ARCHAIC AMPHORAS OF IONIA - Denker, A.; Oniz, H. (Copernicus Gesellschaft Mbh, 2015)
Few other regions offer such a rich collection of amphoras than the cities of Ionia. Throughout history amphoras of these cities had been spread all over the Mediterranean. Despite their common characteristics, amphora manufacturing cities of Ionia had their own distinctive styles that can be identified. They differed in details of shape and decoration. Each city produced an authentic type of amphora which served as a trademark of itself and enabled its attribution to where it originated from. That's why, amphoras provide important insight into commerce of old ages and yield evidence into ancient sailing routes. Owing to this our knowledge of the ancient trade is profoundly enriched. The following is based on the finds of amphoras which originated from the Ionian cities of Chios, Clazomenai, Lesbos, Miletus, and Samos. Starting from city-specific forms which offer interpretative advantages in provenancing, this article surveys the salient features of the regional forms and styles of the those Ionian cities. 3D modeling is utilized with the aim of bringing fresh glimpses of the investigated amphoras by showing how they originally looked. Due to their virtual indestructibility these models offer interpretative advantages by enabling experimental testing of hypotheses upon the finds without risking them. The 3D models in the following sections were reconstructed from numerous fragments of necks, handles, body sherds and bases. They convey in color-unlike the monochrome drawings which we were accustomed to-the texture, decoration, tint and the vitality of the amphoras of Ionia.
Underwater 3D Recording Modeling -- APR 16-17, 2015 -- Piano di Sorrento, ITALY
Keywords: Amphoras; Archaic Period; Ionia; 3d Modeling